Quid Quo Pro. I doosie, You doosie. Which are the language style for kids on series kids? - Amriani, Annisa; Faizal, Abdul Azis (International Journal of Contemporary Studies in Education, 2023)
This study looks at the language style used in series for kids, on title The Boss Baby: Back in Business. To describe how much language style used and the function of language style. Used qualitative research to analysis the dialogue on the series, the researcher discovered language style Apheresis, Bombastic, Simploke, Exclamation, Alusio, and Clinch. And several functions of language style, such as convey mood, persuade the readers or listeners, and to enhance the impact of the ideas presented. As the result, this study concludes that every film or series have language style which are different from each other. However, kids can still enjoy these movies or series with adult supervision